HOTS Based on Revised Bloom's Taxonomy : Analysis in English Examination Test Items Used in High School Level - Sausan, Kania; Rohmatillah, Rohmatillah; Rini, Yulan Puspita (English Education: Jurnal Tadris Bahasa Inggris, 2023)
Today, humans must think critically to face all challenges. In order to improve Indonesia's PISA survey results, the government developed the 2013 curriculum, which emphasizes critical and creative thinking. The aims of this research were to determine the proportion of HOTS and HOTS characteristics reflected in high school English test questions. The objects of the research were the English midterm and final exams for the 10th and 11th grades in the second semester of the 2021–2022 academic year used at MAN 1 Lampung Tengah. This study used a qualitative content analysis design. The study found that in the mid-term 10 grade, there were 6 items, or 20%, labeled "very low," whereas in the mid-term 11 grade, 14 items, or 46.67%, were labeled "enough." For the final Exam 10 class, 5 items were found at 12.50%, referred to as "very low," and 13 items were found at 32.50%, referred to as "low." The outcomes of HOTS-based questions were 86.84%, with questions about critical thinking abilities being the most prominent. This was followed by HOTS questions that help students develop creative thinking abilities (10.52%) and questions that aid in the development of problem-solving skills (2.63%).